DELAYED HEADING DATE1 interacts with OsHAP5C/D, delays flowering time and enhances yield in rice. Issue 2 (4th September 2018) - Zhang, Huan; Zhu, Shanshan; Liu, Tianzhen; Wang, Chunming; Cheng, Zhijun; Zhang, Xin; Chen, Liping; Sheng, Peike; Cai, Maohong; Li, Chaonan; Wang, Jiachang; Zhang, Zhe; et al.
Summary: Heading date is an important agronomic trait affecting crop yield. The GRAS protein family is a plant‐specific super family extensively involved in plant growth and signal transduction. However, GRAS proteins are rarely reported have a role in regulating rice heading date. Here, we report a GRAS protein DHD1 (Delayed Heading Date1) delays heading and enhances yield in rice. Biochemical assays showed DHD1 physically interacts with OsHAP5C/D both in vitro and in vivo . DHD1 and OsHAP5C/D located in the nucleus and showed that rhythmic expression. Both DHD1 and OsHAP5C/D affect heading date by regulating expression of Ehd1 . We propose that DHD1 interacts with OsHAP5C/D to delay heading date by inhibiting expression of Ehd1 .